Personalised cryptographic key generation based on FaceHashing - TEOH, A (2004)
Among the various computer security techniques practice today, cryptography has been identified as one of the most important solutions in the integrated digital security system. Cryptographic techniques such as encryption can provide very Long passwords that are not required to be remembered but are in turn protected by simple password, hence defecting their purpose. In this,paper, we proposed a novel two-stage technique to generate personalized cryptographic keys from the face biometric, which offers the inextricably link to its owner. At the first stage, integral transform of biometric input is to discretise to produce a set of bit representation with a set of tokenised pseudo random number, coined as FaceHash. In the second stage, FaceHash is then securely reduced to a single cryptographic key via Shamir secret-sharing. Tokenised FaceHashing is rigorously protective of the face data, with security comparable to cryptographic hashing of token and knowledge key-factor. The key is constructed to resist cryptanalysis even against an adversary who captures the user device or the feature descriptor. (C) 2004 Elsevier Ltd. All rights reserved.